Pelatihan Pembuatan Bucket Snack dan Strategi Pemasaran Pada Ibu-Ibu PKK Desa Sutojayan Kecamatan Pakisaji Kabupaten Malang - Djapalata, Anggreni Shinta; Nugraha, Danang Aditya; Nage, Vensislaus; Amanda, Kharisma; Cahyani, Indah Ayu (Jurnal Pengabdian Masyarakat Bhinneka, 2022)
Abstract Training on making snack buckets and marketing strategies for PKK women in Sutojayan village can help improve skills, help create jobs among PKK women in Sutojayan village and help boost the economy of PKK women in Sutojayan village. The implementation method used is the survey and coordination stage, the material procurement stage, training and making snack buckets, and strategy and marketing training. This activity was attended by 30 PKK women from Sutojayan village. This training was very useful for PKK women in Sutojayan village, such as having new skills, and knowing how to market their products.